Molecular Clocks in Pharmacology - Musiek, Erik S. (2013)
Circadian rhythms regulate a vast array of biological processes and play a fundamental role in mammalian physiology. As a result, considerable diurnal variation in the pharmacokinetics, efficacy, and side effect profiles of many therapeutics has been described. This variation has subsequently been tied to diurnal rhythms in absorption, distribution, metabolism, and excretion, as well as in pharmacodynamic variables, such as target expression. More recently, the molecular basis of circadian rhythmicity has been elucidated with the identification of clock genes, which oscillate in a circadian manner in most cells and tissues and regulate transcription of large sets of genes. Ongoing research efforts are beginning to reveal the critical role of circadian clock genes in the regulation of pharmacologic parameters, as well as the reciprocal impact of drugs on circadian clock function. This chapter will review the role of circadian clocks in the pharmacokinetics and pharmacodynamics of drug response, and provide several examples of the complex regulation of pharmacologic systems by components of the molecular circadian clock.